DIALOG ANTAR UMAT BERAGAMA - Zainol Hasan (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2018)
The past event is book and history. Both of them are not only scary stories not only for mourned but also for a changing reference. Actulally, this earth is not possible to be transformed quickly, but it can be changed depend on the human’s sprite to determine wheater it is to dezided to be misereble or properity. A conflict between horisontal contardiction and socity should be stop. The human needs peace of life and not disaster. As the result, all of conflick mus be end of, whatever that are elements, such as the conflick between religion and the other one. In addition, a history has already recorded that the distiction of religions have created a lot of problems and victims. It is terrible and irony that the existence of a religion must be a tool and place to peace and safe. However, in this condition is contraray that a religion is being tool to execute each others. Ther are many nation child to be victims and even they are dead without no rasons. This case must be stop. The gate of pluralism is to find Kalimatun Sawa’, a dialuge is to solve relegions problems . In this arena, conflict can be recovered.